OS JINGLES ELEITORAIS NAS CAMPANHAS PRESIDENCIAIS BRASILEIRAS - Manhanelli, Carlos Augusto Bonacorso (2009)
The objective of this work is to rescue the main jingles used in the presidential electoral campaigns with direct vote in Brazil, under the optics of the propaganda and of the political-electoral marketing and inside of the social context of each time, trying to discover what they present in common. The idea is to describe the lyrics of the electoral music and as those lyrics they were used as advertising pieces in the electoral campaigns. To this, it will be made a rising and analysis in audio pieces in the phonographic, in the radio and TV history, in search of those music (jingles), telling the strategies used with those pieces. Researches bibliographical it will be made with the objective of knowing the social and political context of each time to compare the lyric and the rhythm used in each jingle.(AU)